Supporting and sustaining well-being in the workplace : insights from a developing economy - Jayasingam, Sharmila; Omar, Safiah; Mustamil, Norizah Mohd; Hashim, Rosmawani Che; Bakar, Raida Abu (Emerald Publishing Limited, 2020)
Supporting and Sustaining WellBeing in the Workplace: Insights from a Developing Economy explores how our understanding of the human experience at work can be enhanced and how this has broader implications for employee wellbeing. Each chapter covers unique perspectives on issues effecting personal wellbeing, including depression, working conditions that affect home life, mindfulness, and character building at the workplace. Steps and measures that can be used by management to adopt and develop wellbeing practices and actively cultivating a culture that nurtures employees are explored, as the book reflects a dual agenda for healthy working environments through jobs that are designed to promote wellbeing and positive crossover to employee's nonwork lives. Written for academics and practitioners alike, this study presents a unique perspective on this complex and developing area of workplace practice and policy. It draws on examples from an emerging economy using the conservation of resources theory as the foundation to evaluate how the use of pertinent resources creates opportunities for staff to grow and develop as individuals.
Includes index.
Keywords: Work environment -- Psychological aspects.; Job stress.; Industrial safety.; Business & Economics -- Industrial Management.; Personnel & human resources management.; elektronické knihy; electronic books